Soil-transmitted helminth infections and nutritional indices among children (5–9 years) and adolescents (10–12 years) in Calabar, Nigeria - Anok Ukam Usang; Edema Enogiomwan Imalele; Emmanuel Offiong Effanga; Ukoha Kalu Ukoha; Ituna Emini Eleng (BMC Public Health)
Abstract Background Soil-transmitted helminth (STH) infections are a significant public health concern in developing countries, particularly affecting children (5–9 years) and adolescents (10–12 years). This study investigated the prevalence of STH infections, examined associated risk factors, and assessed their impact on the nutritional status of children and adolescents. Methods An analytical cross-sectional study was conducted within schools and took place from April to June 2023 and involved 382 participants in Calabar, Nigeria. All participants in the study completed a questionnaire designed to gather information on their demographics and knowledge, attitudes, and practices (KAP) regarding STH infections. Anthropometric measurements were taken according to World Health Organisation (WHO) standards. Fresh faecal samples were collected from each study participant and examined via the Kato-Katz technique. The data were analysed using STATA software, version 14. A binomial logistic regression model was used to identify predictors of STH infections and to examine the associations between STH infection status and stunting, underweight, and wasting. Results The overall prevalence of STHs was 28.8%, with Ascaris lumbricoides (19.6%) being the most prevalent. The prevalence of STHs was greater among males (30.2%) than females (27.7%) and was relatively greater among participants aged 10 years and above (34.8%). All study participants recorded light infection intensities. The prevalence rates of stunting, underweight, and wasting were 10.5%, 8.4%, and 6.3%, respectively. Respondents with no history of deworming were significantly less likely to contract an STH infection (Odds Ratio: 0.2; 95% Confidence Interval: 0.1–0.4; P < 0.001). The use of pit latrines was associated with a greater likelihood of STH infection (OR: 2.1; 95% CI: 1.3–3.4; P = 0.002). Additionally, respondents with poor attitude scores were significantly less likely to contract an STH infection (Adjusted Odds Ratio: 0.6; 95% CI: 0.4–0.8; P = 0.003), and those over 10 years old (OR: 0.1; 95% CI: 0.04–0.82; P = 0.027) were significantly less likely to be underweight than those aged 5–7 years. There was no association between stunting, underweight, wasting, and STH infection. Conclusion These findings highlight the necessity for an integrated approach to STH management and nutrition initiatives in Nigeria.